Development of a Period-based Psychological Support Model for Athletes (PSMA-P) - Songyu Im; Youngkil Yun (Korea Institute of Sport Science, 2023)
PURPOSE The purpose of this study was to develop a period-based psychological support model for athletes and to establish a system after deducing a psychological support model foreach time period. METHODS In this study, 5 psychological support practitioners were selected as research participants to explore requirements and 4 athletes were selected for the field application of the psychological support model. The requirements for developing the psychological support model were collected through in-depth interviews by the psychological support practitioners. Literature reviews and interviews were conducted to develop the psychological support model. RESULTS The period-based psychological support model consists of orientation, problem exploration, problem clarification, intervention, effect evaluation, and termination. The period of psychological support for athletes was divided into the following: A single-session psychological support, brief psychological support, and seasonal psychological support. The system of period-based psychological support model for athletes is a flow chart that applies the period-based psychological support model from the initiation till the termination of psychological support. CONCLUSIONS The phase of the psychological support model is expected to contribute to the enhancement of the effectiveness of psychological support by establishing a psychological support system for athletes.